2022
DOI: 10.1021/acs.est.2c05925
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Prenatal Exposure to Emerging Poly- and Perfluoroalkyl Substances Associated with E-Waste Dismantling: Chemical Structure-Based Placental Transfer and Health Risks

Abstract: Limited information is available about prenatal exposure to per-and polyfluoroalkyl substances (PFAS) in electronic waste (e-waste) recycling sites. In this study, we determined 21 emerging PFAS and 13 legacy PFAS in 94 paired maternal and cord serum samples collected from an e-waste dismantling site in Southern China. We found 6:2 fluorotelomer sulfonate (6:2 FTSA), 6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA), and perfluorooctanephosphonate (PFOPA) as the major emerging PFAS, regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
(123 reference statements)
0
11
0
Order By: Relevance
“…As reported in Figure G, the q m values vary from 227 to 196 mg g –1 as the pH varies from 5 to 10. Because p K a values for PFBA, PFBS, PFHxS, and PFNA are less than 3, they will be mostly in anionic form in the water solution when the pH of the solution is between 5 and 11. Because, in acidic pH, the amine group is more protonated, the electrostatic interaction will be high between PFNA and FGO-PEI, and the maximum capacity of PFNA adsorption will be higher.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in Figure G, the q m values vary from 227 to 196 mg g –1 as the pH varies from 5 to 10. Because p K a values for PFBA, PFBS, PFHxS, and PFNA are less than 3, they will be mostly in anionic form in the water solution when the pH of the solution is between 5 and 11. Because, in acidic pH, the amine group is more protonated, the electrostatic interaction will be high between PFNA and FGO-PEI, and the maximum capacity of PFNA adsorption will be higher.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a recent report by the Environmental Protection Agency (EPA), 45% of US tap water is contaminated with forever chemicals like per- and polyfluoroalkyl substances (PFAS) . As per the EPA, the concentrations of per- and polyfluoroalkyl substances are higher than the EPA limit (70 ng L –1 ) in ground and surface water systems in 3186 locations in 50 states in the USA. Since 2016, as per US EPA instructions, the industry has been using short-chain homologues of the long-chain PFAS. In 2022, reported data by the US EPA indicated that the concentrations of short-chain perfluorobutanesulfonic acid (PFBS), perfluorobutanoic acid (PFBA), and tetrafluoro-heptafluoropropoxy propanoic acid (GenX) are increasing in environmental samples, which is alarming. Several studies indicate that short- as well as long-chain PFAS can play a major role in hepatic, hematological, and renal cancer. To tackle the PFAS contamination in water challenges, scientists are designing novel adsorbents with high affinity for per- and polyfluoroalkyl substances for PFAS removal from water. Because C–F bonds in per- and polyfluoroalkyl substances can participate in electrostatic, hydrophobic, and fluorophilic interactions, several efforts have been devoted to design new adsorbents to remove PFAS using dipole–dipole, ionic–dipolar, and fluorophilic interactions. However, several reported data show high removal capacity for long-chain per- and polyfluoroalkyl substances, and the removal efficiency decreased significantly for short-chain PFAS. Herein, we have designed a 2D fluorinated graphene oxide (FGO) and polyethylenimine (PEI) based three-dimensional (3D) porous nanopla...…”
Section: Introductionmentioning
confidence: 99%
“…PFAS have been shown to adversely affect several physiological processes and metabolic pathways that are conserved across phyla. Maternal transfer of several PFAS, including emerging PFAS, to fetus has been documented . Identification of trends related to occurrence, fate, behavior, and bioavailability of PFAS is critical to understanding the risks posed by this class of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal transfer of several PFAS, including emerging PFAS, to fetus has been documented. 8 Identification of trends related to occurrence, fate, behavior, and bioavailability of PFAS is critical to understanding the risks posed by this class of contaminants. Further, comparative evaluations of trends support selection of priority PFAS for monitoring programs, which are relevant to risk assessments and implementation of management options.…”
Section: Introductionmentioning
confidence: 99%
“…In China, p -NEOs as well as m -NEOs were ubiquitously found in urine samples of general population (1–97 years) , and blood samples among young adults (22–27 years) . In infants, cerebral vessels, ion transporters, and organs continue to develop; this makes infants, especially the fetus and newborns, more susceptible to the adverse effects of harmful chemicals than adults. , Recent studies also reported that fetal exposure to NEOs is associated with neonatal and congenital disorders, anencephaly, autism spectrum disorders, and tetralogy of fallot . Therefore, infants’ exposure to NEOs is a great concern and has received substantial research attention.…”
Section: Introductionmentioning
confidence: 99%